2021
DOI: 10.1007/s00167-021-06763-w
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular steroid injection at the time of knee arthroscopy increases risk of post-operative infection

Abstract: Purpose To evaluate the risk of post-operative infection after intra-articular steroid injection at the time of knee arthroscopy at a single institution high-volume sports medicine practice. Methods The electronic medical record at a single institution was queried for all patients who underwent knee arthroscopy from 2011 to 2019. Patients were included if they underwent more simple arthroscopic procedures: diagnostic arthroscopy, meniscectomy, loose body removal, synovectomy, or microfracture. Patients were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The results of this analysis suggest that CSI is associated with an increased risk of serious infections requiring a return to the operating room and exhibits both a time-and dosedependent relationships. Corticosteroid injections administered during or shortly after surgery harbour a well-described increased risk of postoperative [28] infection [2,[6][7][8]21]. Multiple explanations for the relationship between postoperative infection and CSIs have been put forth, but no deinitive connection has been identiied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this analysis suggest that CSI is associated with an increased risk of serious infections requiring a return to the operating room and exhibits both a time-and dosedependent relationships. Corticosteroid injections administered during or shortly after surgery harbour a well-described increased risk of postoperative [28] infection [2,[6][7][8]21]. Multiple explanations for the relationship between postoperative infection and CSIs have been put forth, but no deinitive connection has been identiied.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid injections administered during or shortly after surgery harbour a well‐described increased risk of postoperative [28] infection [2, 6–8, 21]. Multiple explanations for the relationship between postoperative infection and CSIs have been put forth, but no definitive connection has been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, randomised clinical trial results suggest worse outcomes at one year for CSI in the treatment of tennis elbow when compared to placebo (Coombes et al, 2013). Intraarticular CSI at the time of knee arthroscopy increases the risk of post-operative infection (Kohls et al, 2022), and early findings suggest that CSI for knee osteoarthritis may contribute to worsening of the condition as reported in MRI scans (Bharadwaj, 2022) and radiography (Darbandi, 2022).…”
Section: History Of Injectionsmentioning
confidence: 99%
“…Therefore, identifying patients who are at increased risk of this complication and investigating independent risk factors are critical [4][5][6] . One potential risk factor that has historically been described, to increase the risk of infection, is corticosteroid injection at the time of surgery 10,11 . Despite this increased risk, multiple studies have shown that a corticosteroid injection at the time of surgery may decrease postoperative pain, reducing the need for narcotics, reduce heterotopic ossification (HTO) and enhance postoperative function [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%